2010
DOI: 10.5194/acp-10-4823-2010
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of molecular iodine in the marine boundary layer: the link to macroalgae and the implications for O<sub>3</sub>, IO, OIO and NO<sub>x</sub>

Abstract: Abstract. Discrete in situ atmospheric measurements of molecular iodine (I 2 ) were carried out at Mace Head and Mweenish Bay on the west coast of Ireland using diffusion denuders in combination with a gas chromatography-mass spectrometry (GC-MS) method. I 2 , IO and OIO were also measured by long-path differential optical absorption spectroscopy (LP-DOAS). The simultaneous denuder and LP-DOAS I 2 measurements were well correlated (R 2 =0.80) but the denuder method recorded much higher concentrations. This can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 52 publications
6
46
2
Order By: Relevance
“…Elevated I 2 mixing ratios of up to 302 ppt were observed after the algae had been exposed to air for several hours (Huang et al, 2010b). This behavior differs from the emission characteristics of L. digitata found in laboratory incubation experiments, where I 2 emissions are small or stop completely after prolonged exposure (Dixneuf et al, 2009;Ball et al, 2010;Nitschke et al, 2011).…”
Section: Introductioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Elevated I 2 mixing ratios of up to 302 ppt were observed after the algae had been exposed to air for several hours (Huang et al, 2010b). This behavior differs from the emission characteristics of L. digitata found in laboratory incubation experiments, where I 2 emissions are small or stop completely after prolonged exposure (Dixneuf et al, 2009;Ball et al, 2010;Nitschke et al, 2011).…”
Section: Introductioncontrasting
confidence: 38%
“…In recent years, numerous studies have shown that the coastal particle bursts are closely linked to iodine emission from low-tidal macroalgae exposure (e.g., McFiggans et al, 2004;Sellegri et al, 2005;Saiz-Lopez et al, 2006a;Huang et al, 2010c;McFiggans et al, 2010). A clear negative correlation between IO (the precursor of IOP) and tidal height, and a positive correlation between IO and solar irradiation, have been observed (Carpenter et al, 2001;Saiz-Lopez et al, 2006b;Huang et al, 2010b;Commane et al, 2011). The emission of iodocarbons such as CH 2 I 2 from macroalgae was first proposed to be the source of photolabile iodine (Hoffmann et al, 2001;Carpenter, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, studies at other coastal locations have reported a daytime maximum of 25-29 pptv through integrated long-path differential optical absorption spectroscopy (LP-DOAS) measurements at Mace Head (Saiz-Lopez and Huang et al, 2010), 115 pptv using in situ measurements at Mace Head (Saiz-Lopez et al, 2006), 87 pptv at Mweenish Bay-I and 302 pptv Mweenish Bay-II, both close to Mace Head using in situ techniques (Huang et al, 2010), 32 pptv (integrated) and 50 pptv (in situ) at Roscoff (Mahajan et al, 2009;McFiggans et al, 2010), and 3 pptv (in situ) at Scripps Pier, La Jolla, California (Finley and Saltzman, 2008). The peak I atom mixing ratio of 10 ± 5 pptv is lower than a maximum of 22 pptv reported by Bale et al (2008) at Mace Head.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of I 2 have so far been reported at three different mid-latitudinal coastal locations: Mace Head, Ireland (SaizLopez and Peters et al, 2005;Huang et al, 2010), California, USA (Finley and Saltzman, 2008) and Roscoff, France (Mahajan et al, 2009;Leigh et al, 2010). However, detection of I atoms has only been reported by Bale et al (2008) at Mace Head.…”
Section: Introductionmentioning
confidence: 98%
“…Measurements of tropospheric IO have been mostly located in mid-latitude marine coastal areas such as Mace Head, Ireland (Alicke et al, 1999;Saiz-Lopez and Plane, 2004;Huang et al, 2010) and Roscoff, France (Peters et al, 2005;Wada et al, 2007;Whalley et al, 2007;Mahajan et al, 2009) where its detection is conditioned to the biogenic activity when some species of algae are exposed to the atmosphere, emitting mainly I 2 at low tide (Saiz-Lopez and Plane, 2004). Therefore, the concentrations of IO measured in these field campaigns are highly variable (between 1 and 9.8 pptv).…”
Section: Introductionmentioning
confidence: 99%